INVESTIGATION OF THE COMPRESSIVE STRENGTH OF CORAL AGGREGATE CONCRETE USING CORALLINE LIMESTONE AS COARSE AGGREGATE - Alva Yuventus Lukas; Jusuf W. M. Rafael; Maria Y. M. Making; Dewi A. I. Wuwur (Jurnal Pensil : Pendidikan Teknik Sipil, 2025)
Utilization coral limestone aggregate as a sustainable alternative in the construction industry has become critical in order to reduce reliance on traditional aggregates. Previous research Lukas A. Y, et al. revealed that concrete with fine aggregate of zone IV gradation and coarse aggregate coralline limestone replacing 25% coarse aggregate gravel can raise compressive strength concrete to 33.37 MPa. It is predicted that fine aggregate with a zone IV gradation, which has small particle sizes, will fill voids in concrete, enhancing its strength. However, increasing coralline limestone component to 50% reduces concrete compressive strength. This suggests that macroscopically, fine particles of zone IV grading have yet to make a significant contribution to increase in concrete compressive strength. Therefore, the current study attempts to optimize concrete mix employing fine aggregate with zone II gradation and its impact on concrete compressive strength. Meanwhile, study employs a laboratory experimental test for compressive strength and ultrasonic pulse velocity, with a target concrete compressive strength of 30 MPa. Study found concrete with coralline limestone content of 0%, 5%, 25%, 50%, and 75%, as well as fine aggregate from zone II grading, had 28-days compressive strengths of 20.27 MPa, 22.10 MPa, 23.80 MPa, 24.42 MPa, and 18.19 MPa. Fine aggregate in Grading Zone II reduces concrete strength.